Arrhythmogenic Remodeling of β2 Versus β1 Adrenergic Signaling in the Human Failing Heart. (April 2015) - Lang, Di; Holzem, Katherine; Kang, Chaoyi; Xiao, Mengqian; Hwang, Hye Jin; Ewald, Gregory A.; Yamada, Kathryn A.; Efimov, Igor R.
<x xml:space="preserve">Abstract</x> Background— Arrhythmia is the major cause of death in patients with heart failure, for which β-adrenergic receptor blockers are a mainstay therapy. But the role of β-adrenergic signaling in electrophysiology and arrhythmias has never been studied in human ventricles. Methods and Results— We used optical imaging of action potentials and [Ca2+]i transients to compare the β1- and β2-adrenergic responses in left ventricular wedge preparations of human donor and failing hearts. β1-Stimulation significantly increased conduction velocity, shortened action potential duration, and [Ca2+]i transients duration (CaD) in donor but not in failing hearts, because of desensitization of β1-adrenergic receptor in heart failure. In contrast, β2-stimulation increased conduction velocity in both donor and failing hearts but shortened action potential duration only in failing hearts. β2-Stimulation also affected transmural heterogeneity in action potential duration but not in [Ca2+]i transients duration. Both β1- and β2-stimulation augmented the vulnerability and frequency of ectopic activity and enhanced substrates for ventricular tachycardia in failing, but not in donor, hearts. Both β1- and β2-stimulation enhanced Purkinje fiber automaticity, whereas only β2-stimulation promoted Ca-mediated premature ventricular contractions in heart failure. Conclusions— During end-stage heart failure, β2-stimulation creates arrhythmogenic substrates via conduction velocity regulation and transmurally heterogeneous repolarization. β2-Stimulation is, therefore, more arrhythmogenic than β1-stimulation. In particular, β2-stimulation increases the transmural difference between [Ca2+]i transients duration and action potential duration, which facilitates the formation of delayed afterdepolarizations.